Zabiegi retoryczne w dyskursie politycznym, czyli jak powiedzieć wszystko, co trzeba i tylko to, co trzeba? - Kukieła, Elwira (Acta Universitatis Lodziensis. Folia Linguistica, 2010)
The article shows complicated structure of present political language (on example of debates coming from TV programme What is with Poland?). Essential role in the rhetorical structure of political statements, in showing material, plays rhetorical holds, comparisons, metaphors, numerous epithets or evaluation lexemes and the suitably shaped arguments.